Microorganisms as an Indicator of Hygiene Status Among Migrant Food Handlers in Peninsular Malaysia - Woh, P.Y.; Thong, Kwai Lin; Lim, Yvonne Ai Lian; Behnke, J.M.; Lewis, J.W.; Mohd Zain, S.N. (SAGE Publications, 2017)
This study used microbial indicators to assess the hygiene status of 383 migrant food handlers from 3 urban cities in Peninsular Malaysia. Microbiological analysis revealed that all the hand swabs tested 99.5% positive for aerobic plate counts (mean [M] ± standard deviation [SD] = 3.57 ± 0.83 log10CFU [colony forming unit]), 20.8% positive for total coliform/Escherichia coli (M ± SD = 0.30 ± 0.67 log10CFU), and 63.4% positive for Staphylococcus aureus (M ± SD = 1.38 ± 1.26 log10CFU). In addition, aerobic plate counts and Staphylococcus aureus counts exceeded the acceptable standard levels. Bacterial counts were found to be significantly associated with subjects’ country of origin (P = .019) and working responsibilities (P = .001). Our findings indicate high probability of transmission of pathogenic bacteria from the food handlers’ hands to customers during meal preparation and serving. This calls for improvements in personal hygiene and sanitation standards by the relevant health authorities among migrant food handlers.